Bioinspired Janus Textile with Conical Micropores for Human Body Moisture and Thermal Management - Dai, Bing (Advanced materials (Deerfield Beach, Fla.), 2019)
© 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.